2010
DOI: 10.3386/w16060
|View full text |Cite
|
Sign up to set email alerts
|

The Collateral Channel: How Real Estate Shocks Affect Corporate Investment

Abstract: the Haas School of Business at Berkeley, and the University of Naples. We are solely responsible for all remaining errors. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

28
536
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(567 citation statements)
references
References 20 publications
28
536
1
2
Order By: Relevance
“…Gan (2007) finds that Japanese banks that were more exposed to real estate development cut business lending after a sizable fall in aggregate real estate prices. However, Chaney et al (2012) or Cuñat et al (2014) advocate the use of local house prices to study balance sheet effects, as aggregate prices may correlate with macro factors such as exchange rates. Chaney et al (2012) find that shocks to the value of firms' collateral diminish investment while Cuñat et al (2014) document that banks cut their lending in response to local house price drops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gan (2007) finds that Japanese banks that were more exposed to real estate development cut business lending after a sizable fall in aggregate real estate prices. However, Chaney et al (2012) or Cuñat et al (2014) advocate the use of local house prices to study balance sheet effects, as aggregate prices may correlate with macro factors such as exchange rates. Chaney et al (2012) find that shocks to the value of firms' collateral diminish investment while Cuñat et al (2014) document that banks cut their lending in response to local house price drops.…”
Section: Introductionmentioning
confidence: 99%
“…However, Chaney et al (2012) or Cuñat et al (2014) advocate the use of local house prices to study balance sheet effects, as aggregate prices may correlate with macro factors such as exchange rates. Chaney et al (2012) find that shocks to the value of firms' collateral diminish investment while Cuñat et al (2014) document that banks cut their lending in response to local house price drops. We estimate how local house prices and banks' exposure to real estate development affect capital growth, NPLs and loans granted by banks.…”
Section: Introductionmentioning
confidence: 99%
“…2 A formal microeconometric study by Bahaj, Foulis, and Pinter (2015) shows that over 2000-2012 a £100,000 increase in real estate values enabled the representative UK firm to increase investment by about £6,000 pounds and to hire one additional worker. Studies for the US have found similar effects of property prices on investment and entrepreneurship via the collateral channel (Chaney, Sraer, and Thesmar, 2012;Corradin and Popov, 2015).…”
mentioning
confidence: 89%
“…Chaney, Sraer, and Thesmar (2012) and Hilber and Vermeulen (2015) by instrumenting regional house prices by constraints on housing supply. I use measures of regional regulatory constraints, proxied by the rejection rate of planning applications for all developments.…”
mentioning
confidence: 99%
“…For example, Gan [2007a,b] documents reduced lending and firm investment as firms' collateral value and banks' capital deteriorated following the collapse of the Japanese real estate market in the early 1990s. In the period leading to the recent crisis, Chaney et al [2012] find that increased real estate values for companies were related to increases in firm borrowing and investing. It is generally not difficult to link such forces to the events of the recent crisis.…”
Section: Introductionmentioning
confidence: 99%